An Analysis of Code-Mixing Used by the Characters in Beni Setiawan’s Hanum & Rangga: Faith & The City 2018 Movie - Aulia Rahmasari; Nur Rosita (Universitas Negeri Padang, 2022)
The purpose of this research was to find (1) the types of code-mixing used by the characters in the Hanum and Rangga 2018 Movie (2) determine the social factor reaasons of code-mixing. Data source are obtained from the characters’ utterances. The method used in this study is qualitative. Data was analyzed using the theory by Hoffman (1991) for classifying the types of code-mixing. The result of this study shows that three forms of code-mixing have been discovered from three types of Hoffman theory. The researcher discovered that 56 data belong to intra-sentential of code-mixing, 3 data belongs to intra-lexical of code-mixing, and 1 data belongs to involving a change of pronounciation. Intra sentential of code-mixing is the most dominant. Based on the result, the forms of code-mixing dominantly employed by the character in the movie is intra-sentential of code-mixing, whereas involving a change of pronounciation. Moreover, from the 60 data, the researcher also found 20 data is included as social factor of code-mixing and discovered 5 data were included as participant role factors, 4 data belongs to situational factors, 9 data were included as massage-intrinsic factors, and 2 data belongs to language, attitude, dominance, security factors. The reasons for mixing code by the characters include their different background, bilinguals choose their language based on a variety of elements such as who (participants: their histories and relationship), what (subject, content), and when, where a speech act happens.